Feeding ecology of fish - Gerking, Shelby Delos, 1918- (Academic Press, 1994)
Feeding Ecology of Fish establishes a comprehensive framework for the variable ecological patterns exemplified by feeding fishes. The author, a former president of the American Fisheries Society, devotes special attention to synthesizing empirical studies in categorizing feeding patterns. This book shows how remarkably adaptable fish can be with regard to selecting food, often from trophic levels not usually occupied. Relying on a thorough literature survey, Feeding Ecology of Fish will be an invaluable reference for both fishery scientists and ecological theorists.Special features include:* O.